Anterior-oriented proton beams for prostate cancer: A multi-institutional experience. (June 2015) - Cuaron, John J.; Harris, Alexander A.; Chon, Brian; Tsai, Henry; Larson, Gary; Hartsell, William F.; Hug, Eugen; Cahlon, Oren
Abstract Background. Proton beam therapy (PBT) for prostate cancer generally involves the use of two lateral beams that transverse the hips. In patients with hip replacements or a previously irradiated hip, this arrangement is contraindicated. The use of non-lateral beams is possible, but not well described. Here we report a multi-institutional experience for patients treated with at least one non-lateral proton beam for prostate cancer. Material and methods. Between 2010 and 2014, 20 patients with organ-confined prostate cancer and a history of hip prosthesis underwent proton therapy utilizing at least one anterior oblique beam (defined as between 10° and 85° from vertical) at one of three proton centers. Results. The median follow-up was 6.4 months. No patients have developed PSA failure or distant metastases. The median planning target volume (PTV) D95 was 79.2 Gy (RBE) (range 69.7–79.9). The median rectal V70 was 9.2% (2.5–15.4). The median bladder V50, V80, and mean dose were 12.4% (3.7–27.1), 3.5 cm3 (0–7.1), and 14.9 Gy (RBE) (4.6–37.8), respectively. The median contralateral femur head V45 and max dose were 0.01 cm3 (0–16.6) and 43.7 Gy (RBE) (15.6–52.5), respectively. The incidence of acute Grade 2 urinary toxicity was 40%. There were no Grade ≥ 3 urinary toxicities. There was one patient who developed late Grade 2 rectal proctitis, with no other cases of acute or late ≥ Grade 2 gastrointestinal toxicity. Grade 2 erectile dysfunction occurred in two patients (11.1%). Mild hip pain was experienced by five patients (25%). There were no cases of hip fracture. Conclusion. PBT for prostate cancer utilizing anterior oblique beam trajectories is feasible with favorable dosimetry and acceptable toxicity. Further follow-up is needed to assess for long-term outcomes and toxicities.